2021
DOI: 10.1111/jan.15125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exergaming on functional outcomes in people with chronic stroke: A systematic review and meta‐analysis

Abstract: Aims:The aim of this review is to synthesize and evaluate effectiveness of exergaming on balance, lower limb functional mobility and functional independence in individuals with chronic stroke. Design:The present review is a systematic review and meta-analysis. The review is written in accordance with the guidelines from the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) Data Source: Searches were conducted across seven databases (PubMed, EMBASE, Web of Science, CINAHL, CENTRAL, Scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…Based on results from studies with exergame trainings in healthy older adults or other neurological patients, superior effects on cognitive functions of the additional exergame training compared to usual care alone are hypothesised (37,38,126). Previous research has shown that exergame training may have positive effects on gait and mobility (29,33), including gait speed, spatiotemporal gait parameters, and mobility in chronic stroke. Therefore, superior improvements in various spatiotemporal gait parameters and mobility in the intervention compared to the control group are expected in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on results from studies with exergame trainings in healthy older adults or other neurological patients, superior effects on cognitive functions of the additional exergame training compared to usual care alone are hypothesised (37,38,126). Previous research has shown that exergame training may have positive effects on gait and mobility (29,33), including gait speed, spatiotemporal gait parameters, and mobility in chronic stroke. Therefore, superior improvements in various spatiotemporal gait parameters and mobility in the intervention compared to the control group are expected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This is an identi ed need since cognitive dysfunction after stroke has a persistently high prevalence (127)(128)(129). Exergames have the potential to increase motivation for training (34,49), to produce additional bene ts on physical functions as compared with conventional care modes (33,130), as well as on cognitive functions (37,38,131). Exergames that contain aspects of virtual reality have shown to be able to signi cantly effect on Body Structure/Function and Activity level outcomes, including improvements in cognitive function and there is, therefore, evidence supporting the use of such interventions as an adjunct for stroke rehabilitation (47,48).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other low-quality studies have also demonstrated possible bene ts of including CG and gaming devices in stroke rehabilitation (67, 69, 74). A review by Chan et al ( 74) looked solely at exergaming (video games that require people to interact with the thorough purposeful body movements) at improving functional outcomes in patients with chronic stroke and it was found that exergaming showed statistically signi cant improvement in balance, lower limb functional mobility, and functional independence (74).…”
Section: Virtual Reality Platformmentioning
confidence: 99%